Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2174/1381612822666161027153140
|View full text |Cite
|
Sign up to set email alerts
|

HDL-Targeting Therapeutics: Past, Present and Future

Abstract: Large-scale epidemiological studies firmly established the association between low plasma levels of high-density lipoprotein-cholesterol (HDL-C) and elevated risk of cardiovascular disease. This relationship is thought to reflect the key biological function of HDL, which involves reverse cholesterol transport from the arterial wall to the liver for further excretion from the body. Other aspects of the cardioprotective HDL functionality include antioxidative, anti-inflammatory, anti-apoptotic, anti-thrombotic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In spite of positive effects on LDL‐C and triglycerides, we observed a significant reducing effect of ALE on serum HDL‐C concentrations. However, the observed reduction was mild, and it should be noticed that the causal association between pharmacological modulation of HDL‐C levels and cardiovascular risk is uncertain (Zakiev, Feng, Sukhorukov, & Kontush, ). Finally, ALE may exert an indirect effect on the improvement in NAFLD indices, as the body mass index fell in those receiving ALE supplementation, and weight loss is a recognized therapy for NAFLD (Clark, ).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of positive effects on LDL‐C and triglycerides, we observed a significant reducing effect of ALE on serum HDL‐C concentrations. However, the observed reduction was mild, and it should be noticed that the causal association between pharmacological modulation of HDL‐C levels and cardiovascular risk is uncertain (Zakiev, Feng, Sukhorukov, & Kontush, ). Finally, ALE may exert an indirect effect on the improvement in NAFLD indices, as the body mass index fell in those receiving ALE supplementation, and weight loss is a recognized therapy for NAFLD (Clark, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several therapeutic approaches have been developed in order to maintain a proper level of HDL cholesterol. Statins are drugs able to determine a substantial reduction of LDL concentration [31]. Similarly, fibrates can lead to a moderate increase of HDL-C levels ranging from 5 to 15% [32,33].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, the elevated HDL-C has been linked to the lower risk of coronary heart diseases due to its involvement in reverse cholesterol transport (Ali et al, 2012;Zakiev et al, 2017). In this study, it is observed that HFD decreased the serum HDL-C, which is markedly increased by the peel extracts of lime, sour orange and pomello at both 250 mg kg −1 and 500 mg kg −1 .…”
Section: Discussionmentioning
confidence: 60%